2013
DOI: 10.1371/journal.pone.0082495
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Evolution and Diversity of Conus Peptide Toxins, as Revealed by Gene Structure and Intron Sequence Analyses

Abstract: Cone snails, which are predatory marine gastropods, produce a cocktail of venoms used for predation, defense and competition. The major venom component, conotoxin, has received significant attention because it is useful in neuroscience research, drug development and molecular diversity studies. In this study, we report the genomic characterization of nine conotoxin gene superfamilies from 18 Conus species and investigate the relationships among conotoxin gene structure, molecular evolution and diversity. The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
6
22
2
Order By: Relevance
“…A previous analysis of patterns of conotoxin divergence suggested that introns within contoxoin gene superfamilies were similar across species within a gene superfamily (Wu et al 2013). Our results partially corroborate this suggestion, as the ratio of exon to noncoding divergence depended on what conotoxin region was encoded by the exon.…”
Section: Conotoxin Molecular Evolutionsupporting
confidence: 88%
See 4 more Smart Citations
“…A previous analysis of patterns of conotoxin divergence suggested that introns within contoxoin gene superfamilies were similar across species within a gene superfamily (Wu et al 2013). Our results partially corroborate this suggestion, as the ratio of exon to noncoding divergence depended on what conotoxin region was encoded by the exon.…”
Section: Conotoxin Molecular Evolutionsupporting
confidence: 88%
“…In addition, the number of exons per gene within a gene superfamily align with results previous studies based on a relatively smaller number of sequences (Wu et al 2013;Barghi et al 2015a). For example, Barghi et al (2015a) found that the J superfamily consisted of a single exon and (Wu et al 2013) found several gene superfamilies (i.e., I1, I2, and M) consisting of three exons, which are identical to the results presented here.…”
Section: Conotoxin Genetic Architecturesupporting
confidence: 86%
See 3 more Smart Citations